Frequency and Effective Factors on Discontinuation of Treatment in Patients with Inflammatory Rheumatic Diseases - Maryam Mobini; Reza Ali Mohammadpour; Mohammad Reza Biabani (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Treatment of rheumatic diseases depends on proper use of medications. The aim of this study was to evaluate the frequency and reasons for discontinuation of drugs in these patients. Materials and methods: A cross-sectional study was performed in patients with inflammatory rheumatic diseases in Sari, Iran 2020-2021 to investigate the frequency and reasons for discontinuation of drugs. Statistical analysis was performed using SPSS V20 and descriptive statistical methods were used to determine the frequency of drug discontinuation and its causes. Results: The participants (n=251) included 197 patients with rheumatoid arthritis, 31 with systemic lupus, 16 with ankylosing spondylitis, and 7 patients with psoriatic arthritis. The mean age of patients was 52.36±13.4 and mean duration of illness was 8.35±7.31 years. Drug discontinuation was seen in 73 patients (85 cases). The most common reason for drug discontinuation was drug side effects (55.4%). Drug shortage, transient improvement of symptoms, ineffectiveness of the drug, and fear of developing COVID 19 were some of the reasons for discontinuation of drug. Conclusion: The most common cause of discontinuation of treatment was drug side effects, but in about one third of cases, there are factors that could be corrected to help preventing drug discontinuation and non-adherence to treatment.